1994
DOI: 10.1080/01688639408402664
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of attention: Relationship between psychological testing and information processing approaches

Abstract: Examined the relationship between the psychological testing and information processing approaches in assessing attention. Eighty-seven subjects (57 females, 30 males) undertook eight psychological tests of attention and a visual-spatial reaction-time task. Using the cognitive-correlate method (Posner & McLeod, 1982), it was found that three components of attention (viz., visual-motor scanning, sustained selective processing, and visual/auditory spanning) derived from the psychological tests could be significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…This finding is contrary to the work of others (Shum et al, 1990;Shum et al, 1994) and may be due to the small group size in the present study. Within the control group, consistency as well as length of the warning appeared to have an effect, but there was no apparent interaction.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…This finding is contrary to the work of others (Shum et al, 1990;Shum et al, 1994) and may be due to the small group size in the present study. Within the control group, consistency as well as length of the warning appeared to have an effect, but there was no apparent interaction.…”
Section: Discussioncontrasting
confidence: 85%
“…While the information processing model of Shum et al (1994) demonstrates the separate stages, it does not necessarily follow that each stage is unitary. If manipulations of more than one task variable impair the same stage it is possible that two or more processes are involved.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Completion of Trails A involves complex visual scanning, motor speed and agility 23,24 as participants draw lines to connect consecutively numbered circles as quickly as possible. Completion of Trails B requires the additional processes of cognitive flexibility and set-shifting 10,25 as participants connect circles in an alternating sequence of numbers and letters, linking them in ascending order as fast as possible (1-A-2-B-3-C, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have used motor tasks such as tapping and placing pegs (Fuller & Jahanshahi, 1999). In most cases, these tasks are not attentional tasks (Shum, McFarland, & Bain, 1994). These studies have reported sometimes contradictory findings about divided attention among patients with schizophrenia.…”
mentioning
confidence: 99%